Strategi Perencanaan Konten Radio Menara FM Bali Dalam Program “Milis” - Bidayanti, Made Putri; Alit Suryawati, I Gusti Agung; Amanda Gelgel, Ni Made Ras (E-Jurnal Medium, 2021)
One of the oldest radios in Bali is Menara FM Bali radio, which has been established since October 9, 1971 which was then chosen as the subject of research to know the process of preparing a radio content planning strategy. With the aim to know the strategy of planning radio content of Menara FM Bali in the MILIS program. In fact the most popular program ini Radio Menara FM Bali is a MILIS whose content planning successfully achieves the destination of the radio where the program is sheltered. This research uses descriptive qualitative research method using Philip Lesly's theory. The results of the research showed Philip Lesly's theory in accordance with the content planning strategy of Radio Menara FM Bali, which was done not because of the scientific basis in the field of broadcasting or communication but in accordance with the needs in the field.   Keyword : Radio, Menara Bali FM, Content Planning, MILIS